2021
DOI: 10.3390/coatings11020181
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Selection of Data Processing Methods for the Application of Cr3+ Photoluminescence Piezospectroscopy to Thermal Barrier Coatings

Abstract: Thermal barrier coatings (TBCs) are an indispensable part of the blades used in aeroengines. Under a high-temperature service environment, the thermal oxidation stress at the interface is the main cause of thermal barrier failure. Cr3+ photoluminescence piezospectroscopy has been successfully used to analyze the thermal oxidation stress of TBCs, but systematic and quantitative analysis results for use in data processing are still lacking, especially with respect to the identification of peak positions. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The thermal oxidation stress in TGO can be expressed as: where Π U is the piezospectroscopic coefficient under a uniaxial stress state. The piezospectroscopic coefficients Π U of TGO were 2.71 ± 0.04 cm −1 /GPa and 2.50 ± 0.05 cm −1 /GPa for R1 and R2, respectively [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal oxidation stress in TGO can be expressed as: where Π U is the piezospectroscopic coefficient under a uniaxial stress state. The piezospectroscopic coefficients Π U of TGO were 2.71 ± 0.04 cm −1 /GPa and 2.50 ± 0.05 cm −1 /GPa for R1 and R2, respectively [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…PLPS technology has a wide application in stress characterization and debonding detection of TBCs [ 29 , 30 , 31 , 32 , 33 , 34 ]. Cr 3+ PLPS technology has been widely used to characterize the TGO stress [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the TGO can be regarded as a thin film, the stress state is presumed to be a biaxial in‐plane equal biaxial stress state (i.e., σ 11 = σ 22 , σ 33 = 0). Therefore, the simplified relationship between the wavenumber shift of the ruby fluorescence peak and the stress of the TGO layer is almost homologous with that of Eu 3+ photoluminescence given in Equation () 35,65 . For ruby photoluminescence piezospectroscopy, the piezo‐spectroscopic coefficients under a uniaxial stress state (П U ) were calibrated as in a previous study 65 and were −2.71 ± 0.04 cm −1 /GPa and −2.50 ± 0.05 cm −1 /GPa for R 1 and R 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the simplified relationship between the wavenumber shift of the ruby fluorescence peak and the stress of the TGO layer is almost homologous with that of Eu 3+ photoluminescence given in Equation ( 6). 35,65 For ruby photoluminescence piezospectroscopy, the piezo-spectroscopic coefficients under a uniaxial stress state (П U ) were calibrated as in a previous study 65 and were −2.71 ± 0.04 cm −1 /GPa and −2.50 ± 0.05 cm −1 /GPa for R 1 and R 2 , respectively. Three measuring points were randomly selected on the surface of TBC specimens after thermal cycles to collect ruby fluorescence spectra, as shown in Figure 6.…”
Section: Thermal Oxidation Stressmentioning
confidence: 99%
“…Data processing methods (Lorentzian, Gaussian, pseudo-Voigt (Psd-Voigt) functions, and the barycenter method) were used to identify the positions and intensities of the characteristic peaks in the spectra taken from samples with external or internal stress. For example, Lu et al [45] compared the fitting results using different functions and found that the Lorentzian method was the most applicable and contributed to improving the stress measurement precision in the TGO layer based on Cr 3+ photoluminescence piezospectroscopy. However, there is still a lack of specific studies on the effectiveness and applicability of data processing methods for the high-resolution stress analysis of the TBC layer using Eu 3+ photoluminescence piezospectroscopy.…”
Section: Introductionmentioning
confidence: 99%